2000
DOI: 10.1677/erc.0.0070243
|View full text |Cite
|
Sign up to set email alerts
|

The role of inhibins and activins in prostate cancer pathogenesis.

Abstract: Successful prostate cancer diagnosis and management continue to provide challenges for the clinician. While interventions aimed at the containment of both early and late disease continue to fail in a significant number of patients, the search for answers must incorporate an analysis of the processes of normal and aberrant growth and development within the gland itself. Inhibin and its structurally related protein, activin, are members of the transforming-growth-factor β (TGFβ) superfamily. Originally identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 86 publications
1
19
0
Order By: Relevance
“…Furthermore, mean Activin A serum concentrations were significantly more elevated in PC patients than in BC patients. This latter phenomenon further indicate, as reported in other studies, that Activin A may be actively involved in the modulation of the osteoblastic activity which, in the case of prostate cancer, is predominant and may account for osteoblastic reactions induced by tumor cells [8,12,23,31,32]. In addition, our results have highlighted that, in PC patients Activin A levels significantly correlated with PSA serum concentrations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, mean Activin A serum concentrations were significantly more elevated in PC patients than in BC patients. This latter phenomenon further indicate, as reported in other studies, that Activin A may be actively involved in the modulation of the osteoblastic activity which, in the case of prostate cancer, is predominant and may account for osteoblastic reactions induced by tumor cells [8,12,23,31,32]. In addition, our results have highlighted that, in PC patients Activin A levels significantly correlated with PSA serum concentrations.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies suggest that Activin A may have a role in tumor progression [2,3,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The specific [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the relevance to innate immunity lends credence to early hypotheses of metabiomic relationships in initiating various neoplasias (35,37), including that of the prostate. Of note, the activin/TGF-b signaling subnetwork has already been acknowledged to be important in prostate carcinogenesis (38). We have shown that D12S297 harbors the human activin receptor, ACVR1B, which has been described as having somatic mutations and deletions in at least 4 other types of cancers, and which is expressed in prostate epithelium (39).…”
Section: Discussionmentioning
confidence: 72%
“…There are several currently known mechanisms for the prostate cancer pathogenesis [7]. Mutation of P53, common in prostate cancer, influenced its downstream effectors, which have been proved mediating prostate cancer processing and causing aberrant nuclear protein accumulation [8][9][10].…”
Section: Introductionmentioning
confidence: 99%